Henri Matisse's medical history: Multiple health problems and impact on creativity. (May 2021) - Zeidler, Henning
Matisse (1869–1954) is regarded—along with Pablo Picasso—as one of the most influential contemporary artists of the 20th century. Books, biographies and illustrations often show the artist in a wheelchair or in bed, producing cut-papers with a pair of scissors or painting with a specially extended brush. Usually it is reported that abdominal surgery left Matisse chair- and bed-bound. The life of Matisse was marked by various further health problems that have never been considered in full in a medical journal. Moreover, his biography is full of examples of the reverse interaction between health and art, whereby not only health problems influenced his art but also how his artistic activity had an impact on his health and mental condition. Therefore, a comprehensive view on the relationship between health and art in the life and art of Matisse is attempted here. Matisse's medical history not only provides an instructive example of life-long multiple somatic and psychosomatic health issues, but also contributes to the humanistic view of medicine by demonstrating how he impressively captured the problems of his artistic work and life through vitality and creative power.